Оптимізація системи автоматичного керування подачею живильного розчину в теплицях - Синявський, О. Ю.; Савченко, В. В. (Енергетика і автоматика, 2017)
OPTIMIZATION OF THE AUTOMATIC CONTROL SYSTEM FOR nutrient solution supply IN THE GREENHOUSE A. Sinyavsky, V. Savchenko In greenhouses, watering plants is fed with a nutrient solution through an automatic drip irrigation system. Watering of plants is often carried out according to the given agronomic program depending on the intensity of solar radiation. When applying the system of drip irrigation, the loss of mineral fertilizers and water is not less than 25 %. The purpose of the study is to optimize the system of automatic control of the moisture content of mineral wool. The automatic humidity control system of mineral wool works in automatic mode - according to the signals of the primary humidity converter of the substrate, which enter the regulator, which controls the actuators, and according to the time program from the watering machine. To measure the humidity of the substrate, the UHF-moisture of the mineral wool of the IMESG design was selected. The executive mechanism is a pump with an electromagnetic valve. Since for the object of control of the ratio τ/T<0,2, position regulation is most appropriate. When choosing the law of regulation it is necessary to take into account that for the drop irrigation the entire area of the greenhouses is divided into sections that are consistently fed with nutrient solution. Therefore, based on the dynamic properties of the control object, taking into account the existing technology of feeding the nutrient solution in the greenhouse, the relay-pulse regulation law is most desirable. The relay-pulse regulator can be represented as a series of connected non-linear elements, the simplest element and the forming circle. The system for automatic control of moisture content of mineral wool is nonlinear and discrete, characterized by the presence of delayed units. For its analysis, the theory of nonlinear pulsed automatic control systems was used. For the quality indicator, when optimizing the system of automatic humidity control of the substrate, a total square deviation was adopted. As a result, the impulse duration was determined for the system of automatic control of the mineral wool moisture and time interval quantization. The studies of stability of the system of automatic regulation of moisture content of the substrate were conducted. It is established that the condition of absolute stability of the nonlinear impulse system is fulfilled at the calculated parameters of the adjustment of the regulator. Conclusions As a result of the conducted researches of the system of automatic control of feeding nutrient solution in greenhouses it was established that the deviation of mineral wool moisture from the given value does not exceed 5 %, which corresponds to the agrotechnical requirements. The obtained dependencies that make it possible to determine the parameters of the relay-pulse regulator adjustment for a static object of the first order with delay can be used for a wide class of static objects, since their transfer functions in most cases are approximated by the aperiodic first-order and late-link links.